Business. One: One. Advanced: student's book - Appleby R. Rachel; Bradley J. John; Leeke N. Nina; Scrivener J. Jim (Oxford Businees English)
Business one:one is the first business English course written specifically for teaching and learning one-to-one. You choose what the course covers, what happens in each lesson, and how you practise between lessons. What do you want from your course? Use the free MultiROM to select the topics you need to cover from the How to ... course syllabus.Then use the interactive Learning planner to create your own course plan. What do you do in the lesson? Your 45-60 minute lesson starts with the target language. You decide what happens next. Choose from: communicative tasks like speaking or writing. discussing grammar or collocations in the Language box, talking through helpful ideas in the Hint section. Then use the Lesson record to collate the most useful language from each lesson. It's easy to look it up at any time. What happens between lessons? Use the Listening bank, the Email practice, or the Interactive tests and Grammar on the MultiROM. Explore the Discussion bank topics for more speaking practice.